PENGARUH PERENCANAAN ANGGARAN, KUALITAS SDM, PEMAHAMAN ATAS SISTEM AKUNTANSI, LINGKUNGAN BIROKRASI DAN KOMITMEN ORGANISASI TERHADAP TINGKAT PENYERAPAN ANGGARAN SKPD KOTA LANGSA - Ayuti Ferry Aldita; Said Muniruddin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The purpose of this study is to examine the effect of budget planning, human resources quality, understanding of the local financial accounting system, bureaucracy environment, and organizational commitment on the budget absorption rate of government work units in Langsa city, Aceh. The low absorbtions of the budget is an important issue. This is because the low budget absorption impact on the bad public services and non-fulfillment of economic growth assumptions. This is a hypothesis testing research which is based on the data that collected by questionnaires and analyzed using multiple linear regressions. The number of respondents as many as 68 people. Every SKPD represented by two members, which is 34 SKPD Finance Administration Officer (PPK) and Acting Manager of Technical Activities (PPTK) as respondents. s. The data analysis was carried out by using SPSS (Statistical Package for Social Science) version 22. The results show that (1) budget planning, human resources quality, understanding of the local financial accounting system, bureaucracy environment, and organizational commitment simultaneously have an influence on the effectiveness of the budget absorption rate of government work units in Langsa city, Nanggroe Aceh Darussalam, (2) Partially, budget planning, human resources quality, understanding of the local financial accounting system, bureaucracy environment have positive influence on the budget absorption rate of government work units in Langsa city, Aceh.